Present-day pathophysiological concept of functional dyspepsia - I. V. Mayev; D. N. Andreev; Yu. A. Kucheryavy; D. T. Dicheva; Yu. S. Subbotina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To present modern data on the pathophysiological mechanisms causing functional dyspepsia (FD) syndrome.Key points. Nowadays FD is considered to be a complex multifactor process which cause and effect relationships are under continuous active study. Disorders of stomach motility (delay of evacuation, disorders of relaxation accommodation) and sensitivity (visceral hypersensitivity to distention) are considered to be the basic pathophysiological mechanisms of FD. These changes develop approximately in 40% of FD patients. Besides that, alteration of duodenal sensitivity to hydrochloric acid and lipids can play significant role in genesis of FD.Conclusion. Mechanisms of FD are based on multiple heterogenous disorders of motor and sensitive functions of the stomach and duodenum. Due to major role of stomach motility disorders prokinetics are the priority drugs for treatment of FD.